The Pain and Sleep Questionnaire Three-Item Index (PSQ-3): A Reliable and Valid Measure of The Impact of Pain on Sleep in Chronic Nonmalignant Pain of Various Etiologies - Lindsay E Ayearst; Zoltan Harsanyi; Kenneth J Michalko (Pain Research and Management)
BACKGROUND: Sleep disturbance is among the more common complaints reported by chronic pain patients. Because pain-related sleep disturbance may serve as a marker for the assessment of responses to treatment for chronic pain, inclusion of a measure designed to assess the impact of pain on sleep in clinical trial protocols is important, if not necessary. Measures typically used for this purpose lack scales specifically designed for the assessment of the impact of pain on sleep or are based on a single item. Single-item scales lack reliability and, therefore, validity.